2021
DOI: 10.1073/pnas.2022887118
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of heterochromatin in domain-size-dependent bursts

Abstract: Methylation of histone H3K9 is a hallmark of epigenetic silencing in eukaryotes. Nucleosome modifications often rely on positive feedback where enzymes are recruited by modified nucleosomes. A combination of local and global feedbacks has been proposed to account for some dynamic properties of heterochromatin, but the range at which the global feedbacks operate and the exact mode of heterochromatin propagation are not known. We investigated these questions in fission yeast. Guided by mathematical modeling, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…They suggested that the reader-writer-eraser capacity of HMEs may generate positive feedback loops and cooperative effects in the system that are essential to provide stability to the local epigenetic state. Applications of such formalism, contextualized to specific marks at specific loci, have shown that it is fully consistent with many experimental observations (13,14,17,(20)(21)(22)(23)(24). However, quantitative comparisons with experiments are still rare in particular on how epigenetic marks organize around the nucleation sites, which may bring crucial information on the spreading and maintenance mechanisms (15,25).…”
Section: Introductionsupporting
confidence: 68%
“…They suggested that the reader-writer-eraser capacity of HMEs may generate positive feedback loops and cooperative effects in the system that are essential to provide stability to the local epigenetic state. Applications of such formalism, contextualized to specific marks at specific loci, have shown that it is fully consistent with many experimental observations (13,14,17,(20)(21)(22)(23)(24). However, quantitative comparisons with experiments are still rare in particular on how epigenetic marks organize around the nucleation sites, which may bring crucial information on the spreading and maintenance mechanisms (15,25).…”
Section: Introductionsupporting
confidence: 68%
“…In particular, the study ( Erdel et al., 2020 ) has shown that the HP1 concentration in heterochromatin (of ∼3 μM ( Müller-Ott et al., 2014 )) is well below the half-saturation concentration for in vitro droplet formation of ∼40–45 μM. Moreover, an experimental study by ( Nickels et al., 2021 ) suggests that heterochromatin propagates in sudden bursts at different time intervals with HP1 H3K9me reader responsible for this bursting behavior. In agreement with this recent evidence, our simulations demonstrate that a stable highly condensed chromatin state for kilobase-size chromatin regions can be achieved even at a typical cellular HP1 concentration of 2.65 μM, after broadly varying lag times.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we would also like to mention mesoscopic models that go beyond a lifetime of a single nucleus in order to probe the dynamics of the establishment of heterochromatin compartments and mechanisms of propagation of "epigenetic memory" through cell divisions Ng et al ( 2018 A recent study employing experiment and mathematical modeling Nickels et al (2021) has looked at the fission yeast cell, which contains nucleation center of heterochromatin CenH. By incrementally varying the meting region size, the mathematical model aided by the experiments has come across a remarkable finding that heterochromatin propagation occurs in an all-or-none fashion, where the entire domains collapse abruptly.…”
Section: Mesoscale Models Of Phase Separation and Dynamics Of Chromat...mentioning
confidence: 99%
“…In conclusion, we would also like to mention mesoscopic models that go beyond a lifetime of a single nucleus in order to probe the dynamics of the establishment of heterochromatin compartments and mechanisms of propagation of “epigenetic memory” through cell divisions Ng et al (2018) ; Feinberg and Irizarry (2010) ; Himeoka and Kaneko (2020) ; Nickels et al (2021) . Mathematical models formulated as kinetic monte carlo Dodd et al (2007) ; Nguyen et al (2021) or agent-based Sneppen and Ringrose (2019) dynamical simulations have been widely used to study the stochastic dynamical interplay of local and global feedback mechanisms of histone methylation and acetylation along the 1D genomic sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation